Ireland and the British Empire - Kenny, Kevin, 1960- (Oxford history of the British Empire companion series., 2004)
This is the first comprehensive history of Ireland and the British Empire. It examines the different phases of Ireland's colonial status from the seventeenth century until the present, along with the impact of Irish people, politics, and nationalism on the Empire at large. The result is a new interpretation of Irish history and its place in the rise, expansion, and decline of the British Empire. - ;Modern Irish history was determined by the rise, expansion, and decline of the British Empire. And British imperial history, from the age of Atlantic expansion to the age of decolonization, was moul.